An ideal remuneration model in the peruvian fashion sector - Vargas Paima, Kimberly (2023)
This article aims to establish and regulate ideal remuneration in the Peruvian fashion sector. The Peruvian textile sector is one of those with the highest informality rate, this causes fashion companies to hire personnel (such as designers, workers, textile workers), the same who do not receive remuneration according to their long hours of work. The fashion world not only studies problems with brands or designs, but also studies the problems that arise behind the catwalks, in the preparation of a garment or accessory, even in the way of marketing garments in the market textile. The sale of a garment would not be possible without the creative, technical, and professional capacity of designers or preparations. But how to design an attractive work environment? with ideal remuneration because it would generate greater competitiveness in the textile market.